Perceived Impacts of Radical Land-Use Reform and Equitable Land Distribution on Agrifood Value-Chain Governance and Resource-Based Conflict Reduction among Rural Farmers in Imo State, Nigeria - M.N, Osuji; J.U, Chikaire; C.C, Ejiogu; E.U, Omeire; Adaigho; E, Nmor; E, 6Emerhirhi; V.A, Udensi; U.E, Ahuchaogu; H.I, Duruanyim; et al. (The Bioscan, 2026)
One of the major problems of agriculture in Nigeria and Africa in general is the issue of land tenure arrangement. The way land is owned has prevented would-be enterprising farmers from investing in agriculture. Therefore, a reform of the land tenure arrangements is proposed as the assured answer by this research to the land problem. A total of 300 farmers were selected in Imo State, Nigeria for study. Questionnaire and oral discussions were used to elicit information from the farmers. Data gathered were analyzed using mean and percentages. Results showed the various agrifood value chain activities, such as processing /value addition (93%), marketing (96%), post-harvest management (94.6%) among others. The various forms of land reform as perceived by the respondents include transferring land ownership to small farmers (95.3%), land taxation (88%) and consolidation of holdings (83.3%) among others. Land reform/distribution can significantly guarantee improved agrifood system by guaranteeing secure land tenure and rights (M= 2.43), access to infrastructure (M=2.48), improves input supply (M=2.54), reduces post-harvest losses (M=2.57) among other roles. Land reform reduces conflicts by clarifying and recognizing rights to land (M=2.30), reduces overlapping/multiple claims(M=2.51), supports land-use planning and zoning(M=2.48). The above guarantees farmers heavy investments in agriculture for optimization of production and increase yield for sales to the markets and for family consumption. However, farmers face the following challenges accessing and using land: lack of secure land rights (M=2.47), customary norms(M=2.60), high cost of land (M=2.58), and small and fragmented holdings (M=2.61).